Spreading Buddha’s Word in East Asia: The Formation and Transformation of the Chinese Buddhist Canon, edited by Jiang Wu and Lucille Chia. - Barrett, T.H. (Buddhist Studies Review, 2017)
Spreading Buddha’s Word in East Asia: The Formation and Transformation of the Chinese Buddhist Canon, edited by Jiang Wu and Lucille Chia. Columbia University Press, 2016. XXII + 405pp. Hb. £52.00. ISBN-13: 9780231171601.